ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN BELANJA MODAL TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH PADA PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2012-2017 - Afifah Fauziah Amalia N; Haryanto Haryanto (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to analyze effect of district own revenue, general allocation fund, and capital expenditure on the local financial independen level at the district town in Province of Central Java. This research using a quantitative approach with descriptive of analysis. The sampling technique used in this research is total sampling technique, so that the total sample in this research were 35 districts/cities in Province of Central Java during 2012-2017. This research using a secondary data from The Realization of Regional Budget Reporting that was reported to the Audit Board of Semarang City. The selected analytical method is a multiple linear regression analysis method with hypothesis testing using the T test and significance level of 0.05. The conclusion of the results in this research that is district own revenue has a significant positive effect on the local financial independen level, general allocation funds have a significant negative effect on the local financial independen level, and capital expenditure hasn’t effect on the local financial independen level.